Descriptions of Child Developmental Disorders Living Around Gold Mining - Ernawati Ernawati; Adi Heru Sutomo; Indwiani Astuti; Enda Silvia Putri; Suci Eka Putri; Marniati Marniati; Itza Mulyani (Universitas Teuku Umar, 2024)
Living around the gold mining area, at risk of exposure to mercury (Hg). Pregnant women exposed to Hg alkyl can cause fetal brain damage so that the baby is born with d efects. This is due to the target toxicity of Hg, especially the organic metal compounds are the nervous system. Based on a child development screening questionnaire, ±100 children were questioned about their development, motor development, language and social interaction. This research was to see a picture of the development of children living around the Gold Mining village of Kalirejo, Kokap district, Kulon Progo District, Yogyakarta. The Longitudinal Observational Research Method with serial measurement measured the level of child development in five domains: cognitive, linguistic, motor, social, emotional and behavioral (adaptive behavior) with the Bayley Scale of Infant and Toddler Development Third Edition (BSID III) against 16 infants in the age range of 2-14 weeks (stage I) and 14-26 weeks. (tahap II). The baby's development observations resulted in an average composite development score of 85. Stage I obtained composite scores of cognitive domain; 102.81, language; 107.38, motor: 98.94, social emotional: 100,63 and behavioral: 90.00, while Stage II of each domain had the same scores as 105.94 : cognitive, 105.38: language, 104.81: motor, social-emotional: 98,69 and behavioural: 92.44. The conclusion that the composite child development score was in the average range of 90 - 109 for all domains, means that the child development composite score was still within the normal range (85-115), indicating that there is no developmental impediment. It is recommended to reduce Hg exposure, provide optimal nutrition to the baby and enhance developmental interventions with stimulation to stimulate auditorium, visual, tactile and kinesthetic, thereby improving the quantity and quality of brain cell synapses, to optimize brain function.